Usability Metric Framework in Mobile-Based Waste Management Applications - Nurhayati, Siti; Yuniarno, Saudin; Anandari, Dian (GoAcademica Research & Publishing, 2023)
Measuring usability is an essential task to ensure that an application is accurate, has adequate speed, and also to ensure compliance with user needs. The usability of software plays a primary role in the quality perceived by its users. However, various definitions and related attributes indicate that there is still no standard in this regard. The main objective of this paper is to present the results of a literature review, aiming to showcase all relevant definitions of usability and related attributes introduced to date. This comprehensive view, depicted through a knowledge map based on time, provides an understanding of the observed evolution on one hand, and also serves as a guide for usability measurement attributes on the other hand, to address some non-functional requirements.